Effectiveness of different interventions to reduce occupational sitting among office administrators at Rhodes University - Malesa, Thato (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2020)
Background: Sitting for prolonged periods is common in the working environment. Office workers are exposed to long periods of sitting time at work. Research has reported associations between prolonged sitting and negative health implications. As such studies have proposed different interventions aimed at reducing sitting times in the workplace. The aim of the current study was to evaluate the effectiveness of two different interventions, physical intervention (sit-stand worktables) and personal intervention (instruction to stretch) on compliance and reducing occupational sitting behaviour. The study also aimed to investigate the effectiveness of interventions in improving or impairing mood. Methods: The study took the form of a fieldbased study atRhodes University, Makhanda, South Africa. Fifteen full"“time office workers in different divisions participated in the study. Participants were randomly allocated to either the physical or personal intervention group. In both intervention groups, partic ipants were prompted to stand for five minutes every hour during the workday to either work in a standing position or perform stretches. Over the course of the experiment, desk occupancy, sitting/standing time and mood effect were recorded in both intervention groups Both intervention groups were monitored for a period of three months (58 days). Results: The study found that the physical intervention group was an effective approach to reduce prolonged sitting in the workplace in comparison to the personal intervention group. Over the course of the experiment, there was sustain usage of interventions in both groups, however, in the physical intervention group desk usage decreased overtime. The findings of the study also show that some participants were more compliant with the study procedures than others. It was also found that mood improved upon introducing interventions in the workplace. However, with the outcomes of the results, the study acknowledges that several factors emerged which are likely to impact compliance, which future studies may investigate. Conclusion: Although sit-stand worktables are expensive, it seems like introducing them was successful in reducing sitting time and changing sitting behaviour in comparison to an intervention that instruct s individuals to stand up and stretch.
Keywords: Standing position; Sedentary behavior; Work environment; Employee health promotion; Office furniture -- Design; Industrial hygiene; Employees -- Health risk assessment; Human engineering; Compliance